Experimental approach to suffusion and backward erosion - Chegenizadeh, Amin; Nikraz, H. (2013)
Internal erosion in dams is viewed by engineers as being of particular concern with regard to safety, as there is a danger that there may be no external evidence, or only subtle evidence, that the erosion is taking place. A dam may breach within just a few hours of internal erosion becoming apparent. In order to assist in finding a solution to the lack of external evidence, a series of experimental tests was developed. The tests consisted of applying hydraulic stresses to reconstructed consolidated cohesive soils to evaluate different types of internal erosion (i.e. suffusion and backward erosion). Different parameters such as hydraulic gradient, confining pressure and clay content were examined. When the hydraulic gradient was small, it was concluded that the erosion of the structure's clay fraction was due to suffusion. When the hydraulic gradient increased, it was concluded that the sand fraction erosion commencement was due to backward erosion. Moreover, the clay content was found to be an important parameter leading directly to internal erosion. The effects of confinement on internal erosion, unlike suffusion, increased backward erosion.